A revision of "Cervus" punjabiensis Brown, 1926 (Cervidae, Mammalia) from the Upper Siwaliks of Chandigarh, India. (10th June 2020) - Croitor, Roman; Robinson, Chris
Abstract: This article proposes a revision of the best preserved fossil cervid recovered from the Upper Siwaliks, which, thus far, has been insufficiently described in the literature. The combination of antler and craniodental characters place the deer under study in the genus Metacervocerus, an extinct lineage with a vast Eurasian distribution and a sister phylogenetic relationship with the modern genus Axis . Metacervocerus is distinguished from Axis by its relatively longer upper premolar series and by the form of its second antler bifurcation which has a second tine that is inserted on the anterior side of the main beam. The new examination of the cranial and dental morphology of the specimen from the Siwaliks revealed peculiarities of its cranial and dental morphology that clearly distinguish Metacervocerus punjabiensis from M. shansius from the Late Tertiary of China. The article provides a taxonomic and evolutionary evaluation of craniodental characters of the type specimen of M . punjabiensis, and an analysis of the evolutionary significance of specific antler characteristics, as well as the phylogenetic relationships of the genus Metacervocerus .